2008
DOI: 10.1007/s00586-008-0651-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of bone morphogenetic protein-2 gene polymorphisms with susceptibility to ossification of the posterior longitudinal ligament of the spine and its severity in Chinese patients

Abstract: A case–control study was conducted to examine the association between two single nucleotide polymorphisms (SNPs) in exon 2 of the bone morphogenetic protein-2 gene (BMP-2) and ossification of the posterior longitudinal ligament (OPLL), and to investigate whether SNPs of the Ser37Ala (T/G) and the Ser87Ser (A/G) in the BMP-2 gene are associated with genetic susceptibility to OPLL and its severity in Chinese subjects. The Ser87Ser (A/G) SNP has been implicated in bone mineral density (BMD) and increases the risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 35 publications
1
37
0
Order By: Relevance
“…Whereas this previous study used age-matched unaffected volunteers as the control group, the present study used unaffected family members of OPLL patients as the control. Although the frequencies of the "G" allele of BMP-2 Ser37Ala (T/G), the "T" allele of the COL6A1 promoter, and the "G" allele of COL6A1 intron 33 were similar to those reported in previous studies (Kong et al, 2007;Wang et al, 2008), unaffected family members in our study also exhibited similar allele frequencies (Table 2). This finding raises doubt as to the significance of these four SNPs for OPLL expression.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Whereas this previous study used age-matched unaffected volunteers as the control group, the present study used unaffected family members of OPLL patients as the control. Although the frequencies of the "G" allele of BMP-2 Ser37Ala (T/G), the "T" allele of the COL6A1 promoter, and the "G" allele of COL6A1 intron 33 were similar to those reported in previous studies (Kong et al, 2007;Wang et al, 2008), unaffected family members in our study also exhibited similar allele frequencies (Table 2). This finding raises doubt as to the significance of these four SNPs for OPLL expression.…”
Section: Discussionsupporting
confidence: 87%
“…Genetic polymorphisms in several collagen genes (COL11A2 and COL6A1), which encode for extracellular matrix proteins, have been associated with OPLL (Tsukahara et al, 2005;Kong et al, 2007). The BMP-2 gene, which is a member of the TGF-b superfamily, acts as a potent stimulator of bone formation in vivo and has also been hypothesized to be involved in OPLL pathogenesis (Wang et al, 2008). Human nucleotide pyrophosphatase (NPPS) and its gene have been suggested to play a role in OPLL genetics (Nakamura et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…63 The TC and CC genotypes in exon 3(-726) T/C in the BMP-2 gene of male Han Chinese patients have a genetic susceptibility to OPLL in the cervical spine. 130 Wang et al 129 demonstrated an association between the Ser37Ala (T/G) polymorphism and the occurrence of OPLL. They also showed significant linkage between the Ser87Ser (A/G) polymorphism and the extent of cervical ossification.…”
mentioning
confidence: 99%